Extraction and characterization of pectin from grapefruit (Duncan cultivar) and its utilization as gelling agent - Khan, Ammar Ahmed; Butt, Masood Sadiq; Randhawa, Muhammad Atif; Karim, Roselina; Sultan, Muhammad Tauseef; Ahmed, Waqas (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Globally, agro-industrial by products such as fruit waste has attained immense recognition to be used for the extraction of valuable functional ingredients. Pectin is naturally occurring biopolymer that is widely recognized in food industry as well as in biotechnology. Keeping in view, current research was conducted for extraction, characterization and utilization of grapefruit peel pectin from Duncan cultivar. The extracted pectin was characterized for different parameters that explored its role in value added products. Acid extraction was carried out and then pectin was characterized for equivalent weight, ash content and methoxyl content. With the addition of extracted pectin, jam was prepared and analysed for physicochemical analysis and sensory attributes. The maximum extraction (22.55%) was done from grapefruit peel at temperature-120°C with pH-1.5, while minimum extraction (0.41%) was obtained at temperature-120°C with pH-2. Moreover, adding pectin in jam formulation resulted in significant effect on texture of the final product. Conclusively, pectin holds a great potential to be extracted and utilized in fruit based products for best quality and value addition.